ASSESSMENT OF JUXTA-APICAL RADIOLUCENCY WITH CONE BEAM CT - Sinem Coşkun (Ankara University, 2022)
Aim: This study aimed to investigate the association of JAR with third molar status and mandibular canal and also describe its radiologic features through cone beam computed tomography (CBCT). Methods: CBCT images of 100 individuals (153 mandibular third molars) were evaluated for the presence of JAR. Than, the CBCT images were analysed to evaluate the position of the JAR and its relationship to the impacted teeth, mandibular canal and buccal-lingual cortical plates. Descriptive statistical analyses were used. Results: JAR was identified in 70 individuals and 95 mandibular third molars (48 right side, 47 left side). 22 of the individuals with JAR were male and 48 were female. It was found that 26 (27,4%) of the 95 third molars were erupted, 10 (10,5%) were partially erupted, 59 (62,1%) were impacted. 74,7 % were on the apical third of the root and the rest was located along the mesial or distal surfaces of root. Close proximity to the buccal cortical plate was seen in 25,35 % of JAR located apically, whereas it was seen only 25% of JAR located along the root surface. Only 23.4 % were associated with the mandibular canal. Conclusion: The present study gives an insight into the relationship of JAR with mandibular canal and cortical plates using CBCT. However, future studies are warranted that use a larger sample size to validate the above findings.